Plan de mejoramiento para la empresa A + V FACTORY (2016)
The point of departure for the research and creation of the plan for improvement in the administrative area for the enterprise to V Factory, was the need for the members of this small company looked to increase their profits and take your business to a higher level given the constant and rapid changes of the modern world. The process begins with the assessment and research within the company, allowing to know the internal and external environment of the organization and thus reach conclusive information on the process and throw data; that it will serve to suggest a strategic plan for the administrative area of the company. It continues with the formulation of strategy, which is to develop the company's mission, detect opportunities and external threats to the Organization, define its strengths and weaknesses and establish medium and long term objectives, generate strategies and alternatives, choose tactics to be followed. It continues with the implementation of the strategy; where the company must set annual goals, devise policies, motivate employees and allocate resources, in such a way that allows executing the strategies formulated. It involves developing a culture that hold it. The implementation challenge is to encourage managers and employees to work in the achievement of the objectives of the organization. It concludes with an evaluation of the strategy; which is the means to know when this does not work properly. Strategy is modified in the future, because the internal and external factors change permanently. In this way the company to V Factory leaves a precedent in its development, taking it to have a clear vision and consistent with the new administrative organization.